PENGUKURAN KINERJA DALAM BISNIS INTERNAL DAN KEUANGAN (Studi Kasus Pada Unit Bisnis PT ”Pabrik Sepatu” Sidoarjo) - Musliki Musliki (Sekolah Tinggi Ilmu Ekonomi Indonesia (STIESIA) Surabaya(STIESIA) Surabaya, 2008)
The study of PT Pabrik Sepatu Sidoarjo’s performance process in the internal business and its finance was measured by using 3 phases of opinion approaches. The framework of the first opinion phase simply compared between actual budget on each estimation of group in the loss and profit. The framework of the second opinion phase used management approach by the variant analysis. The analysis is to know each product performance because there are different characteristic and results of operational profit . And in the third phase will be used as an analysis strategic focus. This focuses the cost analysis concept and control operation for strategy followed.The results indicate that product 1 has good enough performance, and product 2 have less gratify performance, while product 3 is very gratifying. This matter affirm that the variance analysis strategic focus represent the appliance of the performance measurement which can give the significant information for the company management